Students’ perceptions of digital technologies’ efficiency for research during and before the COVID-19 era - Sokhulu, Lerato Hlengiwe; Ndebele, Nduduzo C. (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
The COVID-19 pandemic catalysed a rapid shift towards the use of digital technologies in higher education. This prompted the need to explore how digital technologies are used in academic research, propelling a critical examination of their efficiency for postgraduate research purposes. This mixed methods study investigated students' perceptions of digital technologies' efficiency for research during and before the COVID-19 era in two universities in South Africa. A simple random sampling method was utilised to recruit fifty (50) postgraduate student respondents who completed a survey questionnaire designed to capture their perceptions. The survey instrument included items that assessed the ease of access, usability, and overall satisfaction with digital technologies both before and during the pandemic. The quantitative analysis revealed notable shifts in perceptions between the two time periods where participants generally reported an increase in reliance on digital technologies during the COVID-19 period. The increased use of digital technologies as indicated by participants improved access to online databases and other research environments. Nonetheless, challenges such as lack of user training, and technical issues were also highlighted. This study recommends that universities develop user-friendly guides to aid students in independently understanding the use of digital technologies, thus encouraging efficiency whilst promoting self-directed learning.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 9, 2025
Keywords: Academic research; COVID-19 pandemic; Digital technologies; South Africa; Student perceptions; COVID-19 Pandemic -- 2020-2023; Access technologies; Education, Higher -- South Africa; Web-based instruction